SELECTION THE YIELD OF WHEAT (Triticum aestivum L.) LINES IN MIDDLE LAND AND UPLAND - Yulianah, Izmi; Kurnia, Catur Suciari; Kendarini, Niken; Ashari, Sumeru (AGRIVITA, Journal of Agricultural Science, 2012)
Development of wheat can be carried out by cultivating wheat which is able to adapt well and has high productivity in Indonesia. The research was conducted in middle latitude and upland located in Dadaprejo and Cangar with the altitude of 560 m and 1650 m above sea level respectively from May to December 2011. The materials used in this research comprised thirteen wheat lines and two treated varieties. The experiment conducted in each location was arranged using randomly blocked design repeated three times. The data obtained in each location were analysed with variant analysis which was then followed by advanced experiment using 5% LSD. The result showed that six wheat lines were able to adapt and produced higher yields than Selayar varieties in the upland , namely 38, 82, G-17, G-20, H-14, H-19 and in the middle land obtained three lines that is line 82 , G-17 and H-19. Difference of yield decreases between upland and middle land is significant (14.09%).   Keywords: wheat, selection, yield, middle land, upland